Immunogenicity of a CXCL8-based biopharmaceutical drug candidate in comparison to its wildtype form - Talker, Elisa; Gerlza, Tanja; Stas, Philippe; Trojacher, Christina; Adage, Tiziana; Kungl, Andreas J. (Frontiers in Immunology, 2025)
IntroductionChronic inflammatory processes are characterized by the infiltration of chemokine-activated leukocytes into inflamed tissues. Chemokines interact with their respective G protein-coupled receptors (GPCR) on target immune cells as well as with glycosaminoglycans (GAGs), displayed as part of proteoglycans, on the surface of endothelial cells to exert their function. Excessive levels of CXCL8 are associated with several chronic inflammatory diseases, which are characterized by a rich neutrophil influx. The CXCL8-GAG axis therefore represents a new therapeutic route to target these diseases.MethodsAn anti-inflammatory CXCL8-based, dominant-negative mutant chemokine (termed dnCXCL8) with increased GAG binding affinity and knocked out GPCR activity, was generated and was proven to be active in various in vivo models in previous studies. To investigate the immunogenic potential of this dominant-negative mutant in comparison to its wild-type form, an in vitro T-cell activation study was performed.ResultsBoth proteins induced immunogenic responses, with dnCXCL8 showing a slightly higher response than wild-type CXCL8. An increased number of responsive donors for the mutant was detected, but no significant differences were observed at the population level. Concerning protein-derived peptides, the mutant-derived ones showed an enhanced frequency of lymphocyte activation; however, the differences were not significant on the population level.DiscussionThis study provides first insights into the immunogenic potential of a chemokine-based drug candidate and paves the way for further optimization of chemokine-based therapy.